Sea quark polarization and semi-inclusive DIS data - Jiang, X. (2006)
We investigate the potential impact of forthcoming Jefferson Lab semi-inclusive polarized deep inelastic scattering proton measurements in the determination of the sea quark polarization in the nucleons by means of a next to leading order global QCD analysis. Specifically, we estimate the resulting improvement in the constraints on polarized parton densities for different flavors, which is found to be significant for up and strange quarks, and the correlation between remaining uncertainty ranges for each of the parton species.